34. PATIENT'S SATISFACTION WITH THE QUALITY OF REQUIRED SERVICES AT THE MEDICAL CONSULTING DEPARTMENT OF DONG DA GENERAL HOSPITAL HANOI IN 2023 (Vietnam Journal of Community Medicine, 2023)
Purpose: Evaluating the satisfaction of outpatient patients at the Medical Examination Department - Dong Da General Hospital, Hanoi in 2023 Method: The research method of epidemiology with a descriptive cross-sectional study design was selected. Results: The overall patient satisfaction rate with a medical examination and treatment services was not high (62.3%). Among the five aspects, the tangible had the lowest patient satisfaction rate (64.9%). The proportion of patients satisfied with the remaining aspects were, respectively, the trust aspect (70.1%), the responsiveness aspect (62.3%), the assurance aspect (80.1%), and the sympathy (70.1%). Conclusion: The results were found for customers who were not really satisfied with the treatment service. This shows that the hospital needs to improve its medical services in the future to help customers be more satisfied. Recommendation: The hospital needs to purchase new equipment to improve service quality.
Keywords: Satisfaction, Dong Da General Hospital, Tangible aspects.